Pendampingan Teknologi Pengemasan Produk Olahan Mangrove dalam Mendukung Wirausaha Masyarakat - Dody Tri Kurniawan; Ismawati Ismawati; Rika Diananing Putri (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
The activity partner is the Arrahmah women's group, a coastal community of Pinggir Papas who processes mangroves into cookies. This processed mangrove product has relatively low marketing where it is only produced when there is an order for an important exhibition or event. Generally, mangrove cookies are sold in bulk or without packaging. Where the packaging used is plastic packaging without labels or product information. One effort that can support the development of the mangrove cookies business is by providing attractive and informative packaging technology so that it can increase product purchasing power. Partners themselves do not yet have the skills to design attractive packaging that can increase product purchasing power. As is the problem with micro businesses, the skills possessed by partners in entrepreneurship and creating product attractiveness are still low. One effort to improve product marketing is by designing attractive packaging and providing entrepreneurial training to partners. The output of this activity is partner empowerment in the form of increasing entrepreneurial skills and increasing product attractiveness through attractive and informative packaging designs. Other outputs from service activities are online mass media publications and article publications in the national journal ISNN.]